A Review on Medicinal Plants of Natural Origin for Treatment of Polycystic Ovarian Syndrome (PCOS) - Andhalkar, Shivani; Chaware, Vitthal; Redasani, Vivek (Asian Journal of Pharmaceutical Research and Development, 2021)
Polycystic ovarian syndrome (PCOS) related infertility is a global problem that is spreading at an alarming rate. Chronic anovulation, polycystic ovaries, and hyperandrogenism, as well as abnormal menstrual cycles, hirsutism, acne, and infertility, are all symptoms of this condition. PCOS is linked to insulin resistance and elevated levels of male hormones (androgens). Among other things, an inactive lifestyle, a lack of exercise, dietary changes, and stress are all contributing factors. Curcuma longa, Aloe barbadensis, Mentha piperita, Allium fistulosum Cinnamonum zeylanicum, and other plants have been shown to be effective in the treatment of PCOS. The aim of this review is to summarise the most effective medicinal plants that are used in the treatment or prevention of PCOS. Special emphasis is placed on the role of insulin resistance and the possible utility of insulin sensitizers in the treatment of PCOS.